What accounts for the rising share of women in the top 1%? - Richard V. Burkhauser; Nicolas Hérault; Stephen P. Jenkins; Roger Wilkins (Global Labor Organization (GLO), 2020)
The share of women in the top 1% of the UK's income distribution has been growing over the last two decades (as in several other countries). Our first contribution is to account for this secular change using regressions of the probability of being in the top 1%, fitted separately for men and women, in order to contrast between the sexes the role of changes in characteristics and changes in returns to characteristics. We show that the rise of women in the top 1% is primarily accounted for by their greater increases (relative to men) in the number of years spent in full-time education. Although most top income analysis uses tax return data, we derive our findings taking advantage of the much more extensive information about personal characteristics that is available in survey data. Our use of survey data requires justification given survey under-coverage of top incomes. Providing this justification is our second contribution.
Keywords: D31; J16; C81; 330; Top 1%; top incomes; inequality; gender differences; survey under-coverage